BENTUK SAPAAN BAHASA BUGIS DALAM KONTEKS PRAGMATIK GENDER (The Form of Buginese Language Greeting in Gender Pragmatic Context) - Nuraidar Agus (Balai Bahasa Sulawesi Selatan, 2014)
Greeting is one of linguistic marker whose function is the sign of illocution or politeness marker. Besides that, greeting also has function to strengthen communication relationship of interparticipants. The writing is a description of the usage of greeting in interactive communication of interspeakers, of Buginese language based on gender. Therefore, the analysis used is descriptive qualitative method through collecting data on Buginese speaker in triangulation way: observation, interview, and writing note. Some phenomena of male and female speech, are found that both always use different pragmatic greetings. Its result describes that there are four common forms of greeting used by by male and female speakers in Buginese language, those are (1) greeting of vertical and social kinship (2) professional greeting, and (3) solidarity greeting. The phenomena of Buginese greeting usage are different among male and female speakers. Contrastive feature is much influenced by aim, situation, and speech context that become the setting of speech.